Pharmacological Basis for Traditional Use of the Lippia thymoides. (29th March 2015) - Silva, Fabrício Souza; Menezes, Pedro Modesto Nascimento; Sá, Pedro Guilherme Souza de; Oliveira, André Luís de Santana; Souza, Eric Alencar Araújo; Bamberg, Vinicius Martins; de Oliveira, Henrique Ribeiro; Oliveira, Sheilla Andrade de; Araújo, Roni Evêncio e; Uetanabaro, Ana Paula Trovatti; Silva, Tânia Regina dos Santos; Almeida, Jackson Roberto Guedes da Silva; et al.
Abstract : The aim of this study was to evaluate crude extracts and fractions from leaves and stems of Lippia thymoides and to validate their use in folk medicine. In vitro antioxidant and antimicrobial activities and in vivo wound healing in rats, baker yeast-induced fever in young rats, and acute oral toxicity in mice assays were realized. The crude extracts and their dichloromethane and ethyl acetate fractions had potent radical-scavenging activity against the DPPH but were not effective in the β -carotene bleaching method. The dichloromethane fraction from the leaves extract showed the broadest spectrum of activity against S. aureus, B. cereus, and C. parapsilosis . The animals treated with crude extracts showed no difference in wound healing when compared with the negative control group. The crude extract from leaves (1200 mg/kg) has equal efficacy in reducing temperature in rats with hyperpyrexia compared to dipyrone (240 mg/kg) and is better than paracetamol (150 mg/kg). In acute toxicity test, crude extract of leaves from Lippia thymoides exhibited no mortality and behavioral changes and no adverse effects in male and female mice. This work validates the popular use of Lippia thymoides for treating the wound and fever, providing a source for biologically active substances.